2014
DOI: 10.1371/journal.pone.0109122
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome and Small RNA Analysis of Two Chinese Willow Cultivars Reveals Stress Response Genes in Salix matsudana

Abstract: Salix matsudana Koidz. is a deciduous, rapidly growing, and drought resistant tree and is one of the most widely distributed and commonly cultivated willow species in China. Currently little transcriptomic and small RNAomic data are available to reveal the genes involve in the stress resistant in S. matsudana. Here, we report the RNA-seq analysis results of both transcriptome and small RNAome data using Illumina deep sequencing of shoot tips from two willow variants(Salix. matsudana and Salix matsudana Koidz. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…The full genome sequences of S. suchowensis (http://115.29.234.170/willow/)37 and S. purpurea (http://phytozome.jgi.doe.gov/pz/portal.html#) have been released in public databases. In addition, transcriptome analyses of S. matsudana and S. viminalis have been performed to reveal their stress response mechanisms4849. However, no genomic or transcriptomic data have been reported for S. psammophila .…”
Section: Discussionmentioning
confidence: 99%
“…The full genome sequences of S. suchowensis (http://115.29.234.170/willow/)37 and S. purpurea (http://phytozome.jgi.doe.gov/pz/portal.html#) have been released in public databases. In addition, transcriptome analyses of S. matsudana and S. viminalis have been performed to reveal their stress response mechanisms4849. However, no genomic or transcriptomic data have been reported for S. psammophila .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of miRNA expression levels and elucidation of the regulatory relationship between miRNA and its corresponding mRNA target are important to clarify pathways and biological processes including biotic and abiotic stress responses (Rao et al 2014). Transcriptome analyses of P. trituberculatus growth (Lv et al 2015) and responses to salinity challenged (Lv et al 2013) by high-throughput nextgeneration sequencing technology have been reported; however, the study or experimental identification of miRNAs has been no performed.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…They regulate copper homeostasis and stress responses through cleaving the transcripts of PPO genes in P. trichocarpa 1789. Previously, MIR1444 genes were reported only in P. trichocarpa , although the mature sequences of miR1444 had been identified from S. matsudana and various Populus species17111214151617. In this study, we found two MIR1444 genes in various Populus species and one in Salix .…”
Section: Discussionmentioning
confidence: 55%
“…Although its genome has not been sequenced, there are 228.7 million of RNA-seq reads from five illumina runs available (Table S1)1237. Blast analysis of MIR1444 sequences against RNA-seq data of S. matsudana showed the existence of an expressed MIR1444 gene, termed sma-MIR1444 , in S. matsudana (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation